Tìm x: (x-1)+(x-2)+(x-3)+...+(x-100)=50
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(x+1)+(x+2)+(x+3)+...+(x+99)+(x+100)=50
100x+5050=50
100x=-5000
x=-50
\(c,\)\(\left(x-1\right)+\left(x-2\right)+....+\left(x-100\right)=50\)
\(\left(x+x+...+x\right)-\left(1+2+...+100\right)=50\)
\(100x-5050=50\)
\(100x=50+5050\)
\(100x=5100\)
\(\Rightarrow x=\frac{5100}{100}=51\)
\(a,\left(x+1\right)+\left(x+2\right)+\left(x+3\right)+....+\left(x+100\right)=5750\)
\(\left(x+x+x+...+x\right)+\left(1+2+3+...+100\right)=5750\)
\(100x+5050=5750\)
\(100x=5750-5050\)
\(100x=700\)
\(\Rightarrow x=7\)
\(b,x+\left(1+2+3+...+50\right)=2000\)
\(x+\frac{\left[1+50\right]\cdot\left[\left(50-1\right)\div1+1\right]}{2}=2000\)
\(x+1275=2000\)
\(\Rightarrow x=2000-1275=725\)
A = \(\dfrac{3^{100}.\left(-2\right)+3^{101}}{\left(-3\right)^{101}-3^{100}}\)
A = \(\dfrac{3^{100}.\left(-2\right)+3^{100}.3}{\left(-3\right)^{100}.\left(-3\right)-3^{100}}\)
A = \(\dfrac{3^{100}.\left(-2+3\right)}{3^{100}.\left(-3\right)-3^{100}}\)
A = \(\dfrac{3^{100}.1}{3^{100}.\left(-3-1\right)}\)
A = \(\dfrac{3^{100}}{3^{100}}\) . \(\dfrac{1}{-4}\)
A = - \(\dfrac{1}{4}\)
A. \(\left(x+1\right)+\left(x+2\right)+......+\left(x+100\right)=5750\)
\(x+1+x+2+....+x+100=5750\)
\(100x+\left(1+2+3+.......+100\right)=5750\)
\(100x+5050=5750\)
\(100x=700\)
\(x=700:100=7\)
B. x+(1+2+......+100) = 2000
x + 5050 = 2000
x = 2000 - 5050
x= -3050
C. ( x-1 )+(x-2)+......+( x - 100 ) = 50
x-1+x-2+.........+x-100 = 50
100x + ( -1-2-........-100 ) = 50
100x + ( - 5050 ) = 50
100x = 50 + 5050
100 x = 5100
x = 5100 : 100
x = 51
A . \(\left(x+1\right)+\left(x+2\right)+\left(x+3\right)+...+\left(x+100\right)=5750\)
\(\left(x+x+x+...+x\right)+\left(1+2+3+...+100\right)=5750\)
\(100x+5050=5750\)
\(100x=5750-5050\)
\(100x=700\)
\(\Rightarrow x=\frac{700}{100}=7\)
B. \(x+\left(1+2+3+4+5+....+100\right)=2000\)
\(x+\frac{\left(100+1\right).100}{2}=2000\)
\(x+5050=2000\)
\(\Rightarrow x=2000-5050=-3050\)
C. \(\left(x-1\right)+\left(x-2\right)+\left(x-3\right)+....+\left(x-100\right)=50\)
\(\left(x+x+x+...+x\right)-\left(1+2+3+...+100\right)=50\)
\(100x-5050=50\)
\(100x=5100\)
\(\Rightarrow x=\frac{5100}{100}=51\)
a) x . (x - 1) = 0
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x+1=1\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=0+1\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
b) (x - 1)2 = 100
<=> (x - 1)2 = 102
\(\Leftrightarrow\orbr{\begin{cases}x-1=10\\x-1=-10\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=10+1\\x=-10+1\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=11\\x=-9\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=11\\x=-9\end{cases}}\)
a,\(x\left(x-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
b,\(\left(x-1\right)^2=100\)
\(\Rightarrow\orbr{\begin{cases}x-1=10\\x-1=-10\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=11\\x=-9\end{cases}}\)
c,\(x^{50}=x^2\)
\(\Rightarrow x^{50}-x^2=0\)
\(\Rightarrow x^2\left(x^{48}-1\right)=0\)
\(\Rightarrow\hept{\begin{cases}x=0\\x=\pm1\end{cases}}\)
(x - 1) + (x - 2) + (x - 3) + ... + (x - 100) = 50
(x + x + x + ... +x) - (1 + 2 + 3 + ... + 100) = 50
100x - 5050 = 50
100x = 50 + 5050
100x = 5100
x = 5100 : 100 = 51
(x + 1) + (x + 2 ) + (x + 3) + ... + (x - 100) = 50
x - 1 + x - 2 + x - 3 + .... + x - 100 = 50
(x + x + x + ... + x) + (1 - 2 - 3 - ... - 100) = 50
100x + (-2475) = 5750
100x = 5750 - (-2475) = 8225
x = 8225 : 100 = 82,25